2022
DOI: 10.3390/molecules27206806
|View full text |Cite
|
Sign up to set email alerts
|

Hesperetin—Between the Ability to Diminish Mono- and Polymicrobial Biofilms and Toxicity

Abstract: Hesperetin is the aglycone of citrus flavonoid hesperidin. Due to the limited information regarding hesperetin antimicrobial potential and emerging need for novel antimicrobials, we have studied its antimicrobial activity (microdilution assay), antibiofilm activity with different assays in two models (mono- and polymicrobial biofilm), and toxicity (MTT and brine shrimp lethality assays). Hesperetin inhibited growth of all Candida isolates (minimal inhibitory concentration, MIC, 0.165 mg/mL), while it’s inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Previous toxicity studies of hesperidin, hesperetin, and naringenin also supported the results. Although there are previous studies of hesperidin toxicity using in vivo animal modeling and other in vivo animal alternative models, to the best of our knowledge, there is no study with the brine shrimp method where a correlation with the results in the literature exists. …”
Section: Resultsmentioning
confidence: 99%
“…Previous toxicity studies of hesperidin, hesperetin, and naringenin also supported the results. Although there are previous studies of hesperidin toxicity using in vivo animal modeling and other in vivo animal alternative models, to the best of our knowledge, there is no study with the brine shrimp method where a correlation with the results in the literature exists. …”
Section: Resultsmentioning
confidence: 99%
“…Despite the fact that all of these flavonoids have antimicrobial properties, apigenin stood out for having activity against a variety of bacteria and fungi [ 16 ]. Hesperetin, however, has shown extremely significant antifungal action, particularly against the Candida genus [ 124 ]. These chemicals' potent anti-inflammatory effects are primarily attributed to the inhibition of various inflammatory markers, including TNF-α, NF-κB, IL-1β, IL-6, IL-8, and others which are mentioned on these article.…”
Section: Discussionmentioning
confidence: 99%
“…Another research demonstrated the antimicrobial activity of hesperetin where the compound showed antifungal activity against some Candida fungal strains including C. albicans 10/15, C. albicans 10/15, C. albicans 475/15, C. albicans ATCC 10231, C. parapsilosis ATCC 22019, C. tropicalis ATCC 750, C. krusei H1/16, C. glabrata 4/6/15 with a minimum inhibitory concentration (MIC) of 0.165 mg/mL. Also, the compound exhibited antibacterial activity against S. aureus ATCC 11632 with MIC of 4 mg/mL [ 124 ].…”
Section: Biological Activitiesmentioning
confidence: 99%